Sexually dimorphic patterns in maternal circulating microRNAs in pregnancies complicated by fetal growth restriction - Bernadette C. Baker (BMC, 2021)
Highlights Detection and treatment of pregnancies at high risk of fetal growth restriction (FGR) and stillbirth remains a major obstetric challenge; circulating maternal serum microRNAs (miRNAs) offer potential as novel biomarkers. Unbiased analysis of serum miRNAs in women in late pregnancy identified a specific profile of circulating miRNAs in women with a growth-restricted infant. Some altered miRNAs (miR-28-5p, miR-301a-3p) showed sexually dimorphic expression in FGR pregnancies and others a fetal-sex dependent association to a hormonal marker of placental dysfunction (miR-454-3p, miR-29c-3p). miR-301a-3p and miR-28-5p could potentially be used to predict FGR specifically in pregnancies with a male or female baby, respectively, however larger cohort studies are required. Further investigations of these miRNAs and their relationship to placental dysfunction will lead to a better understanding of the pathophysiology of FGR and why there is differing susceptibility of male and female fetuses to FGR and stillbirth.